Analisis Faktor -“ Faktor Yang Mempengaruhi Niat Wajib Wajak Orang Pribadi Untuk Menyampaikan Surat Pemberitahuan Secara Elektronik (E-Filling) - kartika - (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2016)
e-Filing is an innovation that is conducted by DirectorateGeneral of taxes to improve tax administration in Indonesia, a wayof submitting Tax Return (TR) technology-based. Ease of submittingTR technology-based could improve taxpayer compliance in payingtaxes, and it will have an impact to achieve realization target of taxrevenue by Directorate General of taxes. Not only the technicalaspects of developing and applying a technology, but also the socialaspect is another aspect that accompany it, so it can not beseparated from the other one. This research developed andmodified a model of The Theory of Acceptance and Use ofTechnology (UTAUT) by adding some variable like personalcharacteristic and service quality.